Human Merkel cell polyomavirus: virological background and clinical implications. Issue 8 (19th June 2013) - Coursaget, Pierre; Samimi, Mahtab; Nicol, Jérome T.J.; Gardair, Charlotte; Touzé, Antoine
<x xml:space="preserve">Abstract</x> The Merkel cell polyomavirus (MCPyV), identified in humans in 2008, is associated with a relatively rare but aggressive neuroendocrine skin cancer, the Merkel cell carcinoma (MCC). MCC incidence is increasing due to the advancing age of the population, the increase in damaging sun exposure and in the number of immunocompromised individuals. MCPyV must be considered as the etiological agent of MCC and thus is the first example of a human oncogenic polyomavirus. MCPyV infection is common, and seroprevalence studies indicate that widespread exposure begins early in life. The majority of adults have anti‐MCPyV antibodies and there is a growing body of evidence that healthy human skin harbors resident or transient MCPyV suggesting that MCPyV infection persists throughout life. However, the mode of transmission, the host cells, and the latency characteristics of this virus remain to be elucidated. In addition, it is still not clear whether MCPyV is associated with diseases or lesions other than Merkel cell carcinoma. The etiologic role of MCPyV in MCC opens up opportunities to improve the understanding of this cancer and to potentially improve its treatment.